2015
DOI: 10.1038/ncomms7943
|View full text |Cite
|
Sign up to set email alerts
|

Yes-associated protein regulates endothelial cell contact-mediated expression of angiopoietin-2

Abstract: Angiogenesis is regulated by the dynamic interaction between endothelial cells (ECs).Hippo-Yes-associated protein (YAP) signalling has emerged as a key pathway that controls organ size and tissue growth by mediating cell contact inhibition. However, the role of YAP in EC has not been defined yet. Here, we show expression of YAP in the developing front of mouse retinal vessels. YAP subcellular localization, phosphorylation and activity are regulated by VE-cadherin-mediated-EC contacts. This VE-cadherin-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
236
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(264 citation statements)
references
References 47 publications
22
236
0
Order By: Relevance
“…2, panel C) and, concurrently, a YAP nuclear accumulation, which was already reported. 29 This result is consistent with the previously demonstrated competition between EPS8 and YAP for junctional localization. 20 Our findings add further knowledge to a number of recent reports, revealing that the co-transcriptional regulator, YAP, originally characterized as the molecular target of the size controlling Hippo pathway, 21 is a key transmitter of mechanical inputs in gene transcriptional programs.…”
Section: Eps8 As a Novel Component Of Endothelial Adherens Junctionssupporting
confidence: 92%
See 1 more Smart Citation
“…2, panel C) and, concurrently, a YAP nuclear accumulation, which was already reported. 29 This result is consistent with the previously demonstrated competition between EPS8 and YAP for junctional localization. 20 Our findings add further knowledge to a number of recent reports, revealing that the co-transcriptional regulator, YAP, originally characterized as the molecular target of the size controlling Hippo pathway, 21 is a key transmitter of mechanical inputs in gene transcriptional programs.…”
Section: Eps8 As a Novel Component Of Endothelial Adherens Junctionssupporting
confidence: 92%
“…Finally, morphogenetic signals such as Wnt, Rho-GTPases, G-protein coupled receptors (GPCRs), PI(3)K-Akt signaling pathway and mevalonate metabolism modulate YAP phosphorylation and activity. 27,29 We showed that YAP associates with adherens junctions through a-catenin. This association specifically occurs in long confluent monolayers of ECs in vitro (Fig.…”
Section: Structure and Function Of Vascular Endothelial Adherens Juncmentioning
confidence: 99%
“…S7B), suggesting the flow regulation of YAP/TAZ activities does not solely depend on LATS kinases but also through the modulation of Rho-GTPase activities. In addition to the Hippo and Rho-GTPase pathways, other known mechanosensors, such as G protein-coupled receptors and integrins (23,24), and mechanotransduction pathways, including AMP-activated protein kinase, and VE-cadherinmediated phosphatidylinositol 3-kinase (PI3K)/AKT signaling (25,26), have been shown to modulate YAP/TAZ activities through phosphorylation. It would be worthwhile to further delineate the Hippo signaling cascade and the cross-talk between the flow-sensitive pathways that modulate YAP/TAZ activities.…”
Section: Discussionmentioning
confidence: 99%
“…This reflects the potentially detrimental consequences of a deficiency or an excess of blood vessels. The Hippo signaling pathway has been implicated in vascular development (36)(37)(38) but the underlying mechanisms have not been fully described. In this study, we found that the cytoplasmically localized phospho-YAP, which is not involved in transcription, plays an important role in promoting cell migration via activating CDC42.…”
Section: Discussionmentioning
confidence: 99%